Cover Crop and Fertility Effects on Escherichia coli Abundance in a Composted Poultry Litter-Amended Silt Loam Soil. (20th February 2020) - Sarr, Sait; Coyne, Mark; Gebremedhin, Maheteme; Topè, Avinash; Patel, Shreya
Abstract : Soil conservation practices such as cover crops can improve crop production, soil quality, and water quality. Cover crops can also influence soil microbial growth and activity. Cover cropped and manured soils can potentially store and transmit fecal bacteria (e.g., E. coli ) to surface water if runoff and subsurface seepage occur. While many studies have shown the soil health benefits of cover crops, fewer studies have evaluated the extent to which cover crops influence the abundance of potential waste-borne pathogens. A two-year study (2015–2017) was conducted on a limited-resource farm in Logan County, Kentucky, USA, to quantify the abundance of the fecal indicator Escherichia coli ( E. coli ) bacteria (as a proxy for fecal coliforms) in treatments with and without cover crops or composted poultry litter. The cover crop consisted of a cereal rye ( Secale cereale L.), Austrian winter pea ( Pisum sativum L.), and crimson clover ( Trifolium incarnatum L.) mix. Summer crops consisted of a no-till maize ( Zea mays L.)—soybean ( Glycine max L.) rotation. Soil samples were taken before and after each summer crop season and assessed to detect and enumerate E. coli. At the end of the study period, no significant treatment differences in the E. coli abundance in soil were detected (ca. 10 4  CFU·g −1 ) (p > 0.05 ). However, season/time was a significant factor (p < 0.05 ). We conclude that the background E. coli already present in soil was sufficiently high, inhibiting the detection of the influence of added composted litter. These indigenous E. coli were unaffected by cover crop and nutrient management but did fluctuate on a seasonal basis.